Recent progress and approaches on the synthesis of Mn-doped zinc oxide nanoparticles: a theoretical and experimental investigation on the photocatalytic performance. (16th May 2020) - Silva, J. M. P.; Andrade Neto, N. F.; Oliveira, M. C.; Ribeiro, R. A. P.; de Lazaro, S. R.; Gomes, Y. F.; Paskocimas, C. A.; Bomio, M. R. D.; Motta, F. V.
Abstract : Connecting structural, morphological, and electronic features of ZnO:Mn, one improved photocatalyst for dye degradation complemented by DFT calculations. Abstract : Transition metal-doped semiconductors are promising to conduct the future of environmental remediation from photocatalysis. In this study, the role of Mn-doping on the structural, electronic, morphological, optical, and photocatalytic properties of the ZnO matrix was investigated combining experimental and theoretical techniques. The Zn1− x Mn x O ( x = 1, 2, 4, and 8 mol%) samples were obtained using the microwave-assisted hydrothermal (MAH) method, while DFT calculations were carried out to complement the experimental characterization. Structural analysis indicates that Mn-doped samples exhibit structural defects that govern their electronic structure, generating singular band-gap values attributed to the perturbation of electronic levels in the vicinity of the Fermi level. The morphological analysis indicates that the Mn doping modifies the morphology of the ZnO powders exhibiting rods, flower-like, and spherical shapes. From photocatalytic measurements, it was observed that Zn1− x Mn x O ( x = 2 and 4 mol%) performs the best for dye degradation, which was associated with a new distribution of the electronic levels and charge carrier mobility. This combined approach was useful for interpreting the photocatalytic activity of Mn-doped ZnO.